Hubungan Asupan Protein dengan Kejadian Stunting pada Remaja di Sukoharjo Jawa Tengah - Chastity, Canny Nur, Dr. M. Shoim Dasuki, M.Kes (2017)
Background: The prevalence of stunting in Indonesia, in 2013 was 37.2%, which is means it's increase compared to the data from 2010 and 2007. The prevalence of stunting in adolescents aged 13-15 years was 35.1%. It shows the incidence of stunting in adolescents, which is still fairly high enough. The highest protein requirements is in adolescents. Meanwhile, in Central Java, the data shows that the population with Protein Adequacy Score is very less as much as 52.4% experienced by adolescents. The high incidence of stunting and low consumption of protein is a phenomenon that examined in this study. Aim: Understanding the relationship between protein intake with the incidence of stunting in adolescents in Sukoharjo, Central Java. Methods: The type of this research is an analytic observational with case control approach and to sampling using purposive sampling technique. The total sample of 29 adolescents experience stunting and 29 adolescents do not experience stunting that qualified the restriction criteria. Measurements of protein intake patterns using Semi Quantitative Food Frequency, whereas the height measurement using microtoise and classified using a diagram of height for age (H/A) WHO-NCHS. The data was analyzed by comparison test Chi Square. Result: Based on the comparison test Chi Square between protein intake and the incidence of stunting p value = 0.001 and OR = 6.984. Conclusion: Low protein intake is a risk factor for adolescents with stunting at risk by 6.984.